Are social native bees affected by fungal-based biopesticides? - Leite, Mariana Oliveira Garrigós (2023)
With the increasing demand for quality food and the need for a more sustainable agriculture, alternative tactics to chemical control for pest management are constantly advancing, such as using mycoinsecticides. These biopesticides are aligned with productive agriculture that keeps agroecosystem resources and biodiversity safe. However, they are still aimed at controlling insect pests, in the same environment where other non-target insects live. Pollinators, especially the social bees, are essential in agroecosystems, as they promote the maintenance of the surrounding biodiversity as well as increase the productivity and quality of crops due to pollination. Toxicological studies with entomopathogenic fungi and social bees have risen in recent years; however, the vast majority still focus on one species, at the individual level, under laboratory conditions and evaluating mortality rates. In this context, we investigated the possible effects of entomopathogenic fungi on social bees, at the individual and colonial levels, with experiments in the laboratory, semi-field, and natural field conditions. For this, in Chapter 2, we evaluated the lethal effect of topical and oral exposure, with different concentrations, of the fungi Beauveria bassiana, Metarhizium anisopliae, and Cordyceps fumosorosea in two stingless bees from tropical regions, Scaptotrigona depilis and Tetragonisca angustula and two temperate bee species Apis mellifera and Bombus terrestris. In Chapter 3, we evaluated the possible sub-lethal effects of the application of the fungi B. bassiana and C. fumosorosea, both at the individual and colonial level of S. depilis, as well as the efficiency of the hygienic behavior of the bees in their cleaning capacity. Finally, in Chapter 4, we evaluated the effect of applying the recommended field concentration of the fungus B. bassiana in coffee crops on S. depilis colonies. In general, the fungi were lethal to the bees, with varying virulence in relation to the fungus species, bee species, and infection route. Non-lethal effects were also observed; the fungi affected the individual behavior of the S. depilis workers, as well as the growth of brood cells, pollen collection, and garbage removal in the colony. However, when colonies of the S. depilis species were exposed to the fungus under field conditions, in the short term, the colonies did not suffer any effect on any of the evaluated parameters, such as brood cell growth, pollen collection, litter removal, and foraging activity. These results indicates that: (i) toxicological tests of mycoinsecticides should be performed with social insects both in the laboratory and in the field, as the effects at individual and colony level may differ; (ii) toxicological tests should consider other species of social bees, because results might also difer, meanwhile many the other species are important from an ecological and agricultural point of view.